The Impact of Inflation Rates, Interest Rates, and Economic Growth on Stock Prices of Semiconductor Sector Companies for the Period 2022-2023 - Sopiana, yayan; setiawati, ira; widiastuti, tri (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This study aims to analyze the effect of Inflation, Interest Rates, and Economic Growth on the Stock Prices of Semiconductor Companies during the period of 2022-2023. The research method used is quantitative with a causal-comparative approach. The data used is secondary data obtained from official websites such as NASDAQ, Yahoo Finance, and Macrotrends. The population in this study consists of semiconductor companies listed on NASDAQ, with a sample of 9 companies selected using purposive sampling based on specific criteria. The independent variables in this study are Inflation (X1), Interest Rates (X2), and Economic Growth (X3), while the dependent variable is stock prices (Y). The research method utilized is panel data regression with the EViews 13 application. The results of the data analysis indicate that Inflation and Interest Rates have a significant impact on stock prices, while Economic Growth does not have a significant impact on stock prices.